Comparison of application of various anti-fatigue nutritional beverages in supplementing function of basketball players - Wen, Zebin; Wu, Jiaqi (Progress in Nutrition, 2019)
Basketball, as a high-intensity and high-risk sport, requires athletes to maintain a high level of physical function at all times. In recent years, with the rapid development of food manufacturing technology, a variety of anti-fatigue nutritional beverages for athletes emerge one after another. Therefore, the application of a variety of anti-fatigue nutritional beverages in supplementing the different physical function needs of basketball players has become a key topic in sports health research. In this study, basketball players were selected as experimental subjects, and the control group was set up. Three kinds of anti-fatigue nutritional beverages, namely sugar beverage, taurine beverage and tea beverage, were tested to understand the different application of different nutritional beverages in supplementing function, so that basketball players can better maintain physical strength and improve sports performance. Through the comparison of the experimental results, it is concluded that sugar beverage has the greatest application degree to blood lactic acid, taurine beverage has the greatest application degree to liver glycogen content and tea beverage has the greatest application degree to serum urea. Therefore, in practical application, attention should be paid to the coordination of various nutritional beverages and different beverages should be drunk according to the actual needs.